USING REGIONAL RENEWABLE ENERGY RESOURSES FOR HEATING SUPPLY SYSTEMS - Pshinko, O. M.; Gabrinets, V. O.; Kuznetsov, V. H. (Science and Transport Progress, 2017)
Purpose. The study analyzed the possibility and conditions for the effective operation of heating systems during the transition of the heat-generating capacity to biofuels energy. The straw of cereal crops, which are prevailing in Dnipro region, is used for this. The main purpose is scientific calculation of opportunities and cost of specific measures for such a transition. As an example it was taken the boiler-room of campus at Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT) that consumes natural gas. Methodology. The work analyses the legislative base of Ukraine, which promotes the using of renewable energy sources as fuel, as well as the incentive mechanisms for the development of this trend. The paper identifies opportunities of Prydniprovsk region to ensure straw supply for the boiler-room. Cost parameters of cargo transportation on the territory of Ukraine in 2016, which depend on the distance and the size of the trucks, are analysed. These indicators, as well as indicators related to its purchase, are considered together with energy potential of using the straw as fuel. Findings. With existing in Ukraine (as of 2016) the grain yielding capacity in the agriculture and cost indicators in the field of transportations, the transition of capacity share to biofuel is sufficiently profitable. The thermal power unit cost can be reduced fourfold. Originality. For the first time it is proposed to use the new integrated approaches to assess the cost of thermal power unit boiler with its transition to the use of renewable energy sources. The authors also proposed a new logistics delivery of these sources to the place of their application. From a technical and cost points of view it was determined the optimal order of capacity transfer for new renewable sources of energy in a given region depending on the structure of areas under crops and their productivity. Originality. The introduction of the proposed solutions and approaches to capacity boiler renewable energy sources can be realized with a relatively small investment and can provide significant economic benefits.